Altered gut microbial profile is associated with differentially expressed fecal microRNAs in patients with functional constipation - Yao, Junpeng; Yan, Xiangyun; Li, Yanqiu; Chen, Yaoyao; Xiao, Xianjun; Zhou, Siyuan; Zhang, Wei; Wang, Lu; Chen, Min; Zeng, Fang; Li, Ying (Frontiers in Microbiology, 2024)
While dysbiosis within the intestinal ecosystem has been associated with functional constipation (FC), the mechanisms underlying the interactions between FC and the microbiome remain poorly elucidated. Recent investigations suggested that host microRNAs (miRNAs) can modulate bacterial growth and influence the composition of the gut microbiome. To explore the connection between gut microbiota and fecal miRNAs in FC patients, we initially employed 16S rRNA sequencing to assess the gut microbial landscape in 30 FC patients and 30 healthy controls (HCs). The α-diversity within the FC group exhibited some alterations, and the β-diversity significantly differed, signifying distinctive variations in gut microbiota composition between FC patients and HCs. Subsequently, we identified 44 differentially expressed (DE) miRNAs in feces from FC patients and HCs. Through correlation analysis between DE miRNAs and FC-associated microbiota, we detected an interaction involving nine DE miRNAs (miR-205-5p, miR-493-5p, miR-215-5p, miR-184, miR-378c, miR-335-5p, miR-514a-3p, miR-141-3p, and miR-34c-5p) with seven bacterial genera (Oscillibacter, Escherichia.Shigella, UCG.002, Lachnospiraceae_NK4A136_group, Lachnospiraceae_UCG.010, Eubacterium_ruminantium_group and Megamonas), as evidenced by a co-occurrence network. Further, a comprehensive panel of seven diagnostic biomarkers (Oscillibacter, Escherichia.Shigella, UCG.002, miR-205-5p, miR-493-5p, miR-215-5p, and Lachnospiraceae_NK4A136_group) demonstrated robust discriminatory capacity in predicting FC status when integrated into a random forest model (AUC = 0.832, 95%CI: 65.73-98.88). Microbiomes correlating with DE miRNAs exhibited enrichment in distinct predicted metabolic categories. Moreover, miRNAs correlated with FC-associated bacteria were found to be enriched in signaling pathways linked to colonic contractility, including Axon guidance, PI3K-Akt signaling pathway, MAPK signaling pathway, and Hippo signaling pathway. Our study offers a comprehensive insight into the global relationship between microbiota and fecal miRNAs in the context of FC, presenting potential targets for further experimental validation and therapeutic interventions.